'We are naked waitresses who deliver sex': a phenomenological study of circumstantial sex workers' lives. Issue 4 (2nd November 2021) - Curtis, Michael G.; D'Aniello, Carissa; Twist, Markie L. C.; Brents, Barbara G.; Eddy, Brandon
Abstract: Historically, research on the commercial sex industry has focused on the industry's impact on society while overlooking the voices and experiences of sex workers. To explore the lived experience of commercial sex workers, we interviewed ten commercial sex workers about their personal relationships, experience in society, and access to effective clinical treatment. Six themes emerged from our qualitative analysis: (1) financial freedom, entrepreneurship, personal agency and self-exploration, (2) temporal nature of the adult industry, (3) disclosure as a continuously impactful process, (4) compartmentalization as protection, (5) segregation and isolation, and (6) therapeutic experiences and preferences. Participants rejected the absolute victim narrative that is often reflected in media, film, and government-sanctioned actions surrounding the adult industry. Results indicate the need for further research on the relationships of people in the adult industry and provide couple and family therapists with a critical understanding of how authenticity, genuineness, and judgment impact clinical treatment.